2017
DOI: 10.1002/alr.21927
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic optic nerve decompression in patients with idiopathic intracranial hypertension

Abstract: Background The conventional treatment for idiopathic intracranial hypertension involves weight loss, steroids, diuretics, and/or serial lumbar punctures; however, if the symptoms persist or worsen, surgical intervention is recommended. Surgical options include cerebrospinal fluid diversion procedures, such as ventriculoperitoneal and lumboperitoneal shunts, and optic nerve decompression with nerve sheath fenestration. The latter can be carried out using an endoscopic approach, but the outcomes of this techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…56 While the former study did not perform analysis of visual improvement, other meta-analyses have demonstrated an improvement in visual acuity, papilledema, and headache in an average of 47 to 84%, 83 to 97%, and 78 to 88% of IIH patients undergoing transverse venous sinus stenting, respectively (►Tables 3-5). 17,18,[54][55][56][57][58] It should be mentioned that one potential limitation of these findings is that these results are largely only applicable to those with patients who would have been documented with venous stenosis whereas those treated with ONSF or CSF shunting may or may not have demonstrated venous stenosis. Additional studies show venous stenting effectively reduces ICP immediately following the procedure and results in a significantly decreased CSF opening pressure for up to 3 months during the postoperative period.…”
Section: Venous Sinus Stentingmentioning
confidence: 95%
See 3 more Smart Citations
“…56 While the former study did not perform analysis of visual improvement, other meta-analyses have demonstrated an improvement in visual acuity, papilledema, and headache in an average of 47 to 84%, 83 to 97%, and 78 to 88% of IIH patients undergoing transverse venous sinus stenting, respectively (►Tables 3-5). 17,18,[54][55][56][57][58] It should be mentioned that one potential limitation of these findings is that these results are largely only applicable to those with patients who would have been documented with venous stenosis whereas those treated with ONSF or CSF shunting may or may not have demonstrated venous stenosis. Additional studies show venous stenting effectively reduces ICP immediately following the procedure and results in a significantly decreased CSF opening pressure for up to 3 months during the postoperative period.…”
Section: Venous Sinus Stentingmentioning
confidence: 95%
“…These findings can be compared with the results of four meta-analyses from 2007 to 2017 that calculated average improvement in visual acuity ranging from 59 to 85% of IIH patients undergoing ONSF (►Table 3). 17,18,54,55 Additionally, results of the meta-analyses showed average improvement in papilledema and headaches ranged from 80 to 81% and 44 to 81% of IIH patients undergoing ONSF, respectively (►Tables 4 and 5 ). 18,[54][55][56][57][58] While there are few reports of major complications due to ONSF, common minor complications include diplopia, corneal dellen, and tonic pupil.…”
Section: Surgical Management Strategies Optic Nerve Sheath Fenestrationmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge, the endoscopic bilateral optic nerve decompression technique is the least used technique in the literature. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%